2022
DOI: 10.1007/s11064-022-03833-4
|View full text |Cite
|
Sign up to set email alerts
|

GPR137 Inhibits Cell Proliferation and Promotes Neuronal Differentiation in the Neuro2a Cells

Abstract: The orphan receptor, G protein-coupled receptor 137 (GPR137), is an integral membrane protein involved in several types of cancer. GPR137 is expressed ubiquitously, including in the central nervous system (CNS). We established a GPR137 knockout (KO) neuro2A cell line to analyze GPR137 function in neuronal cells. KO cells were generated by genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 and cultured as single cells by limited dilution. Rescue cells were then construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Patients with high GPR137 expression exhibited shorter overall survival time than those with low expression in bladder cancer 30 , 31 . However, other studies reported a different role for GPR137, where it promotes cell cycle exit and neuronal differentiation in neuro2A cells 32 . Our study’s finding of under-expression of GPR137 in PNI patients may be associated with this characteristic.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with high GPR137 expression exhibited shorter overall survival time than those with low expression in bladder cancer 30 , 31 . However, other studies reported a different role for GPR137, where it promotes cell cycle exit and neuronal differentiation in neuro2A cells 32 . Our study’s finding of under-expression of GPR137 in PNI patients may be associated with this characteristic.…”
Section: Discussionmentioning
confidence: 91%